1979
DOI: 10.1007/bf00397222
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the genetic determinant for the SHV-1 β-lactamase

Abstract: In two unrelated plasmids of incompatibility groups FII and N the gene for the SHV-1 beta-lactamase exists as part of a transposable element of molecular weight 9.5 megadaltons. This transposon has moved onto plasmids of at least three incompatibility groups; PI, Ialpha and J. This confirms the suggestion that the recent spread of the SHV-1 beta-lactamase has been associated with the transposition of the genetic determinant of this enzyme between unrelated plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 19 publications
3
28
0
1
Order By: Relevance
“…Having ruled out significant plasmid dissemination, bla SHV-2 gene spread may have been facilitated by the interspecies or interclonal transfer of transposable elements. The role of transposable elements in SHV-2 dissemination can be suggested, as the ancestor gene bla SHV-1 possibly exists as part of a mobile element (32). Moreover, bla SHV-2a has been found to be integrated into the chromosome of a Pseudomonas aeruginosa isolate, with investigators suggesting that the flanking sequences are of enterobacterial origin (26,45).…”
Section: Discussionmentioning
confidence: 99%
“…Having ruled out significant plasmid dissemination, bla SHV-2 gene spread may have been facilitated by the interspecies or interclonal transfer of transposable elements. The role of transposable elements in SHV-2 dissemination can be suggested, as the ancestor gene bla SHV-1 possibly exists as part of a mobile element (32). Moreover, bla SHV-2a has been found to be integrated into the chromosome of a Pseudomonas aeruginosa isolate, with investigators suggesting that the flanking sequences are of enterobacterial origin (26,45).…”
Section: Discussionmentioning
confidence: 99%
“…Purification and further biochemical studies indicated that SHV-type P-lactamases have a wide spectrum of hydrolytic activity towards penicillins and cephalosporins (4). SHV-1 has been associated with an uncharacterized transposon of 14.25 kilobases (kb) (29).…”
mentioning
confidence: 99%
“…The principal 8i-lactamases of 112 such strains from London and 96 strains from Nottingham were identified using isoelectric focusing (16). Initially the enzymes were classified as being either chromosomally or R-plasmid mediated or of indeterminate genetic origin (14,15,18,19,27).…”
mentioning
confidence: 99%